From pan-African congresses to the Organisation of African Unity - (:unkn) unknown (My University, 2022)
The months that follow independences in Africa are rich of diplomatic events between new actors on the international stage. Yet, these interactions, such as those between the so-called Monrovia and Casablanca groups, are usually primarily portrayed as a binary ideological opposition between their most prominent figures (such as Kwame Nkrumah and William Tubman). They actually gathered hundreds of different individuals. Somewere formed following trans-imperial mobility schemes, and had their say in discussing pan-African projectsfrom the early XXth century. This paper evaluates their weight in pan-African congresses from 1900 to the creation of the OAU in May 1963. It also explores how they complement or how they challenge projects led by new heads of states and governments. Trans-imperial mobilities are a key factor in establishing multilateraldiscussions on the continent. It complicates narratives of States that relied heavily on “negative” sovereigntyafter independence to legitimize themselves.
Keywords: African Research